'TAM 112' Wheat, Resistant to Greenbug and Wheat Curl Mite and Adapted to the Dryland Production System in the Southern High Plains. Issue 3 (25th August 2014) - Rudd, Jackie C.; Devkota, Ravindra N.; Baker, Jason A.; Peterson, Gary L.; Lazar, Mark D.; Bean, Brent; Worrall, David; Baughman, Todd; Marshall, David; Sutton, Russell; Rooney, Lloyd W.; Nelson, Lloyd R.; et al.
Abstract : 'TAM 112' (Reg. No. CV‐1101, PI 643143), a hard red winter wheat ( Triticum aestivum L.) cultivar with experimental designation TX98V9628, was developed and released by Texas A&M AgriLife Research in 2005. TAM 112 is an F4 –derived line from the cross U1254‐7‐9‐2‐1/TXGH10440 made at Vernon, TX, in 1992. U1254‐7‐9‐2 is a USDA–ARS germplasm line from the Plant Science and Entomology Research unit, Manhattan, KS, and TXGH10440 is a sibling selection of the cultivar TAM 110. TAM 112 is an awned, medium‐early maturing, semidwarf wheat with red glumes. It was released primarily for its excellent grain yield potential particularly in dryland environments of the southern Great Plains; resistance to stem rust (caused by Puccinia graminis Pers.:Pers. f. sp. tritici Eriks. & E. Henn.), powdery mildew [caused by Blumeria graminis (DC.) E.O. Speer f. sp. tritici Em. Marchal], and greenbug [ Schizaphis graminum (Rondani)]; and good milling and bread‐baking characteristics. Compared with existing hard red winter wheat cultivars at the time of release, TAM 112 is most similar to TAM 110 with respect to area of adaptation and disease and insect resistance, but it has significantly higher yield and better bread‐baking characteristics than TAM 110. Licensed to Watley Seed Company for marketing, TAM 112 is currently one of the most popular hard red winter wheat cultivars adapted to the dryland production system in the Texas High Plains and similar areas in the southern Great Plains.